Analisis Pengaruh Stabilitas Politik Terhadap Keberhasilan Persekutuan dalam Kerjasama Ekonomi Internasional - Fitrah Maya Sari Hasugian; Maya Wulan Dari; Tegar Efraim Gilbert Siahaan; Uswatul Akmalia; Khairani Alawiyah Matondang (CV. Ulil Albab Corp, 2024)
In the fast-paced era of globalization, international economic cooperation plays a vital role in enhancing economic growth and global competitiveness. However, the success of this cooperation is significantly influenced by the political stability of the participating countries. This study aims to analyze the impact of political stability on the success of partnerships in international economic cooperation. Using a qualitative approach, this research employs narrative analysis on data from various documents, such as reports from international organizations, journal articles, and other relevant publications. The findings indicate that political stability fosters a conducive environment for foreign investment, strengthens inter-country trust, and enables active participation in global forums. Conversely, political instability tends to hinder resource allocation, reduce foreign investment interest, and threaten the success of international cooperation. This study concludes that political stability not only supports domestic economic growth but also reinforces the country's position in sustainable global economic cooperation. The study recommends strengthening democratic institutions and increasing public participation as essential steps to maintain long-term political stability.